Leven voor een leer - Monteiro, Marit (Amsterdam University Press, 2024)
In September 1945, Anna Terruwe opened a private psychiatric practice in Nijmegen. She soon came into conflict with church authorities over the moral accountability of Catholics suffering from mental health issues. The dispute centred around the competencies of psychiatrists versus priests. In this book, Monteiro examines Terruwe's role in this fundamental conflict within post-war Dutch mental health care.